2019
DOI: 10.1177/1534734619870086
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Chitosan Gel and Soframycin in the Management of Wounds

Abstract: Wounds and related injuries remain a major cause of death and disability. Healing of wound is a complex, highly regulated process that includes cellular, molecular, biochemical, and physiological events that permit living organisms to repair accidental lesions. Therefore, dealing with wounds has always been a subject of concern to the world, and demand for products in wound management had increased to $9.3 trillion worldwide in the health care industry, affecting economic growth. The present work aimed to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The dorsal region was shaved and one fragment was gently removed from the skin using a 10‐mm diameter circular biopsy (Figure 1). 24 The wound was cleaned with a cotton swab soaked in alcohol followed by the application of the plant extract and 1% Soframycin ointment as positive control 25 on the wound once daily for 15 days starting from the first day of wounding. The control group received all the consistents of ointment except plant extract.…”
Section: Methodsmentioning
confidence: 99%
“…The dorsal region was shaved and one fragment was gently removed from the skin using a 10‐mm diameter circular biopsy (Figure 1). 24 The wound was cleaned with a cotton swab soaked in alcohol followed by the application of the plant extract and 1% Soframycin ointment as positive control 25 on the wound once daily for 15 days starting from the first day of wounding. The control group received all the consistents of ointment except plant extract.…”
Section: Methodsmentioning
confidence: 99%
“…A successful hemostatic effect is completed by chitosan-induced inhibition of plasmin release that prevents clot dissolution. During the inflammation stage, chitosan can assist by avoiding or combating bacterial infection, as its positive charge allows it to bind with negatively charged carbohydrate, lipid and protein residues located on the cell surface of bacteria, consequently inhibiting their growth ( Kim, 2018 ; Khanna et al, 2020 ). Furthermore, chitosan exerts anti-inflammatory effects that reduce inflammatory cytokines, IL-10 and TNF-α, reducing oxidative damage and inflammation ( Yang et al, 2016 ; Mohyuddin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its inherent biocompatibility and nontoxicity, it also possesses effective antibacterial, healing, haemostatic, and analgesic effects associated with the cationic amine group [30]. Khanna et al studied the effect of deacetylation on wound healing [31], and the results of in vivo experiments showed that the higher the degree of deacetylation, the faster the rate of wound surface healing. CS can also be used to prepare different types of dressings, including hydrogels, fibres, films, membranes, scaffolds, and sponges, for various types of wounds; this is convenient for clinical applications [32][33][34].…”
Section: Application Of Cs In Wound Healingmentioning
confidence: 99%